Frequency and Prognostic Relevance of FLT3 Mutations in Saudi Acute Myeloid Leukemia Patients - Ghaleb Elyamany; Mohammad Awad; Kamal Fadalla; Mohamed Albalawi; Mohammad Al Shahrani; Abdulaziz Al Abdulaaly (Advances in Hematology)
The Fms-like tyrosine kinase-3 (FLT3) is a receptor tyrosine kinase that plays a key role in cell survival, proliferation, and differentiation of hematopoietic stem cells. Mutations of FLT3 were first described in 1997 and account for the most frequent molecular mutations in acute myeloid leukemia (AML). AML patients with FLT3 internal tandem duplication (ITD) mutations have poor cure rates the prognostic significance of point mutations; tyrosine kinase domain (TKD) is still unclear. We analyzed the frequency of FLT3 mutations (ITD and D835) in patients with AML at diagnosis; no sufficient data currently exist regarding FLT3 mutations in Saudi AML patients. This study was aimed at evaluating the frequency of FLT3 mutations in patients with AML and its significance for prognosis. The frequency of FLT3 mutations in our study (18.56%) was lower than many of the reported studies, FLT3-ITD mutations were observed in 14.4%, and FLT3-TKD in 4.1%, of 97 newly diagnosed AML patients (82 adult and 15 pediatric). Our data show significant increase of FLT3 mutations in male more than female (13 male, 5 female). Our results support the view that FLT3-ITD mutation has strong prognostic factor in AML patients and is associated with high rate of relapse, and high leucocytes and blast count at diagnosis and relapse.